Audiological characteristics of children with congenital unilateral hearing loss: insights into Age of reliable behavioural audiogram acquisition and change of hearing loss - Zhang, Vicky W.; Hou, Sanna; Wong, Angela; Flynn, Christopher; Oliver, Jane; Weiss, Michelle; Milner, Stacey; Ching, Teresa Y. C. (Frontiers in Pediatrics, 2023)
Objectives The aims of this study were to report the audiological characteristics of children with congenital unilateral hearing loss (UHL), examine the age at which the first reliable behavioural audiograms can be obtained, and investigate hearing changes from diagnosis at birth to the first reliable behavioural audiogram. Method This study included a sample of 91 children who were diagnosed with UHL via newborn hearing screening and had reliable behavioural audiograms before 7 years of age. Information about diagnosis, audiological characteristics and etiology were extracted from clinical reports. Regression analysis was used to explore the potential reasons influencing the age at which first reliable behavioural audiograms were obtained. Correlation and ANOVA analyses were conducted to examine changes in hearing at octave frequencies between 0.5 and 4 kHz. The proportions of hearing loss change, as well as the clinical characteristics of children with and without progressive hearing loss, were described according to two adopted definitions: Definition 1: criterion (1): a decrease in 10 dB or greater at two or more adjacent frequencies between 0.5 and 4 kHz, or criterion (2): a decrease in 15 dB or greater at one octave frequency in the same frequency range. Definition 2: a change of ≥20 dB in the average of pure-tone thresholds at 0.5, 1, and 2 kHz. Results The study revealed that 48 children (52.7% of the sample of 91 children) had their first reliable behavioural audiogram by 3 years of age. The mean age at the first reliable behavioural audiogram was 3.0 years (SD 1.4; IQR: 1.8, 4.1). We found a significant association between children's behaviour and the presence or absence of ongoing middle ear issues in relation to the delay in obtaining a reliable behavioural audiogram. When comparing the hearing thresholds at diagnosis with the first reliable behavioural audiogram across different frequencies, it was observed that the majority of children experienced deterioration rather than improvement in the initial impaired ear at each frequency. Notably, there were more instances of hearing changes (either deterioration or improvement), in the 500 Hz and 1,000 Hz frequency ranges compared to the 2,000 Hz and 4,000 Hz ranges. Seventy-eight percent (n = 71) of children had hearing deterioration between the diagnosis and the first behavioural audiogram at one or more frequencies between 0.5 and 4 kHz, with a high proportion of them (52 out of the 71, 73.2%) developing severe to profound hearing loss. When using the averaged three frequency thresholds (i.e., definition 2), only 26.4% of children (n = 24) in the sample were identified as having hearing deterioration. Applying definition 2 therefore underestimates the proportion of children that experienced hearing changes. The study also reported diverse characteristics of children with or without hearing deterioration. Conclusion The finding that 78% of children diagnosed with UHL at birth had a decrease in hearing loss between the hearing levels at first diagnosis and their first behavioural audiogram highlights the importance of monitoring hearing threshold levels after diagnosis, so that appropriate intervention can be implemented in a timely manner. For clinical management, deterioration of 15 dB at one or more frequencies that does not recover warrants action.